Sartre, imagination and dialectical reason creating society as a work of art - Smidt, Austin Hayden (Reframing the boundaries., 2019)
"There are perpetual debates about the extent of freedom in politics. Are we free to choose? Are we overdetermined by our material conditions? Some hybrid between the two? In this text, Austin Hayden Smidt analyzes an oft-overlooked text by Jean-Paul Sartre in order to ground a logical framework for exploring this problem"--